Does a routine post brush bronchial wash increase the yield in diagnosis of lung cancer? - S., Mathan Raj; Murali, Sowmiya (International Journal of Research in Medical Sciences, 2017)
Background: Lung cancer is the most common cause of cancer-related death in both men and women. 80% of the lung cancers are non-small cell lung cancer (NSCLC) and 20% are small cell lung cancer (SCLC). Flexible fiberoptic bronchoscopy is commonly used for diagnostic and staging purposes. Endoscopically visible abnormalities are approached with traditional biopsy forceps, brushings, and washings. Objectives were to assess the yield of bronchial washings, brush cytology and to compare the yield of pre and post brush bronchial washings. Methods: Patients with suspicion of lung cancer will be subjected to bronchoscopy using flexible fibreoptic bronchoscopy. Multiple procedures performed for the retrieval of tissue samples will include bronchial washings (pre and post brushing), bronchial brushing and endobronchial biopsy. Results: A total of 57 cases were included in the study with 40 (70.2%) males and 17 females (29.8%). The yield of pre-brush bronchial washings, post brush bronchial washings and bronchial brushings were 31.6% (18 of 57), 31.6% (18 of 57) and 61.4% (35 of 57) respectively. Biopsy was positive for malignancy in 11 of 19 (58.2%) cases. Adenocarcinoma was the commonest type seen in 32 (56.1%) patients. Of the 27 cases with endobronchial growth 11 were adenocarcinoma (40.7%). Conclusions: There was no difference between the yield of pre-brush washing and post brush washing. The yield of brush cytology was significantly more than the yield of bronchial washings. There is an increase in the yield after adding both pre and post brush bronchial wash.